PENGARUH AKUNTABILITAS PUBLIK, KEJELASAN SASARAN ANGGARAN DAN PENGENDALIAN INTERN TERHADAP KINERJA MANEJERIAL INSTANSI PEMERINTAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Erica Magdalena; Vince Ratnawati; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The objective of the study is to examine empirically the effect of public accountability, budget goal clarity and internal control to managerial performance of government in the city of Pekanbaru. The population on this study were SKPD at Pekanbaru city, and sampel was determined based on judgement sampling method with 160 respondents. Primary data were used in this research, collected with using questionnaire that sent to top and middle manager at SKPD in the region of Pekanbaru. Multiple regression analysis are used as analysis method with using Statistical Package For Social Science (SPSS) as the tools. The results of this study prove that public accountibility, budget goal clarity, and internal control are significantly effect the managerial performance of government in the city of Pekanbaru. The magnitude of the effect of the contribution of public accountability, budget goal clarity and internal control of the manejerial performance in Pekanbaru of 52.1 %.Keywords : Public Accountability, Budget Goal Clarity, Internal Control and Performance Manejerial